2021
DOI: 10.3390/vaccines9121415
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Rates and Determinants of COVID-19 Vaccine Hesitancy for Adults and Children in the Singapore Population: Strengthening Our Community’s Resilience against Threats from Emerging Infections (SOCRATEs) Cohort

Abstract: COVID-19 vaccines are crucial for achieving sufficient immunisation coverage to manage the pandemic, but vaccine hesitancy persists. This study aimed to investigate the prevalence and determinants of vaccine hesitancy in adults and in parents for vaccinating their children using an integrated social cognition model. A community-based cohort in Singapore [N = 1623] completed a survey (wave 25) between June and July 2021 which measured their risk perceptions, distress, trust, vaccination beliefs, and vaccine int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 62 publications
(105 reference statements)
4
42
2
Order By: Relevance
“…While vaccine development usually takes over 10-15 years to ensure safety and efficacy [55] , [56] , U.S. FDA gave its full approval to the first COVID-19 vaccine on 23rd August 2021, less than two years after SARS-CoV-2 was first identified. Despite proven safety and efficacy of COVID-19 vaccines, low vaccine intent or hesitancy can be attributed to side effects and hasty vaccine development [18] , [57] . Perception towards long-term side-effects and the duration of vaccine effectiveness need to be studied to understand its impact on vaccine intent..…”
Section: Discussionmentioning
confidence: 99%
“…While vaccine development usually takes over 10-15 years to ensure safety and efficacy [55] , [56] , U.S. FDA gave its full approval to the first COVID-19 vaccine on 23rd August 2021, less than two years after SARS-CoV-2 was first identified. Despite proven safety and efficacy of COVID-19 vaccines, low vaccine intent or hesitancy can be attributed to side effects and hasty vaccine development [18] , [57] . Perception towards long-term side-effects and the duration of vaccine effectiveness need to be studied to understand its impact on vaccine intent..…”
Section: Discussionmentioning
confidence: 99%
“…Perceived barriers and perceived benefits were the most common determinants that were significantly associated with vaccine hesitancy. Perceived benefits was inversely associated with COVID-19 vaccine hesitancy in twelve studies [6,[11][12][13][15][16][17][18]20,22,23]. A positive association between perceived barriers and vaccine hesitancy was reported by twelve studies [6,[11][12][13][15][16][17][18][19][20]22,24].…”
Section: Hbm Constructs Associated With Vaccine Hesitancymentioning
confidence: 91%
“…Perceived benefits was inversely associated with COVID-19 vaccine hesitancy in twelve studies [6,[11][12][13][15][16][17][18]20,22,23]. A positive association between perceived barriers and vaccine hesitancy was reported by twelve studies [6,[11][12][13][15][16][17][18][19][20]22,24]. Perceived susceptibility was negatively correlated with COVID-19 vaccine hesitancy in eight studies [10,12,14,[16][17][18]20,23]; however, Chen et al [11] reported a positive correlation between perceived susceptibility and vaccine hesitancy.…”
Section: Hbm Constructs Associated With Vaccine Hesitancymentioning
confidence: 93%
See 1 more Smart Citation
“…The scientific community is convinced that, without a broad and comprehensive vaccination program, it will be impossible to overcome COVID-19. However, following some severe adverse events, a growing lack of confidence developed in many European countries, slowing down the worldwide vaccination program [ 98 , 99 ]. Similar to the case of the definition of the main pathophysiological aspects of the SARS-CoV-2 infection, post-mortem investigations have been instrumental in identifying the cause of death in fatal cases following vaccine administration [ 100 , 101 , 102 , 103 ].…”
Section: The Scovid-19 Pandemic and Its Impact On Forensic Investigat...mentioning
confidence: 99%